Effects of Financial Literacy, Financial Attitude, and Personality on Financial Management Practices - Alfiriana, Novika; Juniar, Asrid; Rafli, Muhammad Raihan (SENTRALISASI, 2025)
The purpose of this study is to investigate the effects of financial knowledge, financial attitudes, and personality on financial management behavior, with self-control serving as a mediating variable. The research focuses on employees of PT Bank KB Bukopin Banjarmasin, particularly in the context of post-merger performance challenges. This study seeks to fill the gap in previous research by integrating cognitive and psychological factors within a formal organizational setting. Using a quantitative explanatory approach, data were collected through a census of 75 permanent employees with a minimum of three years of service. The data were analyzed using Partial Least Squares Structural Equation Modeling to assess both direct and indirect effects among the variables. The findings indicate that FK, FA, personality, and SC significantly influence FMB. Notably, personality has the strongest effect on SC, while FK shows the most substantial direct influence on FMB. The model explains 50.8% of the variance in FMB, confirming SC as a key mediating variable. These results reinforce the Theory of Planned Behavior and suggest that improving financial literacy, fostering positive attitudes, and enhancing self-control are essential strategies for strengthening financial behavior among employees in banking institutions.